2x+3=(1x+-1)

Simple and best practice solution for 2x+3=(1x+-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3=(1x+-1) equation:



2x+3=(1x+-1)
We move all terms to the left:
2x+3-((1x+-1))=0
We add all the numbers together, and all the variables
2x-((x-1))+3=0
We calculate terms in parentheses: -((x-1)), so:
(x-1)
We get rid of parentheses
x-1
Back to the equation:
-(x-1)
We get rid of parentheses
2x-x+1+3=0
We add all the numbers together, and all the variables
x+4=0
We move all terms containing x to the left, all other terms to the right
x=-4

See similar equations:

| 3(6-4x)=-2 | | V(a)=(8+-2×)(6+-2×)(×) | | -1+6(x-3)=14x+5-8x | | (-2x+3)(6x+5)=0 | | 2=-10a-18 | | 8x+10-4x=46 | | -5/6=-3/4a | | 2+3x.X=5 | | n/14=4.5/7 | | 5(c-6)c=c+11(24) | | 8p-5=-77 | | -15a=165 | | -6x-23=-8 | | 7-(b+8)=-14 | | 6x-8=-5x+4 | | 3(x-7+4)=18 | | -6p+7=3+9(p-3)-4(-10+4p) | | 15=5+4(2w-3) | | 8(x+3)+6=86 | | 4/2m=18-2/7m | | 3(x-1)=19+x | | 58=2(1+4b | | 12=6(m+5) | | d+10/2=1 | | r+7-4=-3(1+10r)-(r-6) | | 5x+12=3+6x-x. | | 4(2x-3)=18+8 | | 0.3x-1.5=-2.7 | | -5a+17=-33 | | F(x)=4-10 | | 8z-22=3(3z+12)-2 | | 49x11= |

Equations solver categories